OPTIMIZING TALENT MANAGEMENT FOR CAREER DEVELOPMENT FOR STATE CIVIL SERVANTS IN INDONESIA - Rasmulia Sembiring (SEAN Institute, 2023)
The reform of government bureaucracy in the realm of Human Resources pertains to the management of the State Civil Apparatus in accordance with their respective competencies. Talent management is a comprehensive human resource management framework that encompasses the processes of employee acquisition, development, retention, and placement. This approach is designed to prioritise those with the greatest potential and highest levels of performance through the utilisation of evaluation techniques. This statement provides justification for the adoption of merit-based systems at both institutional and national levels. The primary objective of this study is to examine the most effective practises in talent management that may be employed to facilitate the career advancement of government officials in Indonesia. The present study employs a qualitative methodology, specifically utilising descriptive techniques. The findings indicate that talent management plays a crucial role in the career development of the State Civil Apparatus (ASN), employing a comprehensive methodology that encompasses a well-coordinated sequence of phases. From the identification of talent to the capture of information, each stage assumes a pivotal role in establishing an environment conducive to the development and optimal utilisation of gifted persons. By effectively incorporating talent, ensuring appropriate placement, conducting thorough assessments and providing appropriate rewards, implementing retention and succession planning, and facilitating knowledge capture, ASN may enhance its organisational development, promote progress, and deliver high-quality public services. By implementing this strategy, organisations not only acknowledge and utilise the capabilities of individuals, but also establish a strong basis for enduring sustainability, innovation, and achievement.